STRATEGI PEMERINTAH SURABAYA MEWUJUDKAN KOTA LITERASI - Solehuddin, Solehuddin; Rahmadanik, Dida (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2023)
Literacy, when taken literally, refers to a person's capacity to read and write. People who can read and write are often referred to as literate, while those who are illiterate are referred to as illiterate. Descriptive research methods are used by the author in making this scientific article. The results of the research show that Surabaya, as the first literacy city in Indonesia, has implemented various strategies and initiatives to encourage interest in reading and turn reading into a tradition in society. The literacy program in Surabaya provides positive benefits for the community, by increasing interest in reading, participating in conversations, and developing reading habits. a well-organized literacy movement program has been implemented in the city of Surabaya since 2014, according to a compilation of research articles about the government's goal to make Surabaya a city of literacy. The government's approach to a series of literacy initiatives in Surabaya City seems to have succeeded at the habituation and development stage). Internal and external factors can be used to demonstrate this. Internal factors include lack of interest and motivation in reading for Surabaya residents and inadequate library room infrastructure, which includes incomplete books, outdated books, sloppy bookkeeping, and lack of funds that have not been utilized optimally. The external factor itself comes from family support, which fully supports the existence of literacy programs in this city which aims to foster literacy culture and support for the literacy program of Surabaya City in assisting the implementation of literacy programs. Therefore, it can be claimed that the government's strategy to create a literacy city in Surabaya City is weak or has not been fully realized. Keywords: Strategy; Government; Literacy